The faith of non-surveilled pancreatic cysts: a bicentric retrospective study. Issue 1 (January 2022) - Surci, N.; Marchegiani, G.; Andrianello, S.; Pollini, T.; Mühlbacher, J.; Jomrich, G.; Richwien, P.; Tamandl, D.; Schindl, M.; Bassi, C.; Salvia, R.; Sahora, K.
Abstract: Background: Incidental discovery of pancreatic cystic neoplasms (PCLs) is a common and steadily increasing occurrence. The aim of this study was to investigate a cohort of patients presenting with incidentally detected PCLs which were not included in a surveillance protocol, and to compare their risk of malignant evolution with that of systematically surveilled lesions. Materials and methods: A population of PCLs which did not receive surveillance over a period >10 years (population A) was selected at the Medical University of Vienna. A group of "low risk" branch duct intraductal papillary mucinous neoplasm ≤15 mm in size upon diagnosis undergoing a regular follow-up of at least 5 years at the University of Verona was selected as control (population B). The incidence of pancreatic cancer (PC), cumulative risk of PC and disease-specific survival were compared. Results: Overall, 376 patients with non-surveilled PCLs were included in study group A and compared to 299 patients in group B. This comparison resulted in similar incidence rates of PC (1.6% vs 1.7%, p = 0.938), a strong similarity in terms of disease-specific mortality rates (1.3% vs 0.3%, p = 0.171) and the 5- and 10-year cumulative risk of PC (≅ 1% and 2%, p = 0.589) and DSS (≅ 100% and 98%, p = 0.050). Conclusion: The "price to pay" for a negligence-based policy in the population of non-surveilled PCLs was reasonable, and the incidence of PC was comparable to that reported for a population of low-risk cysts enrolled to a standardized surveillance protocol.